Theoretical analysis of expansion process of wet water vapor in working chamber of piston long-stroke linear drive of compressor unit - A. A. Kapelyukhovskaya; G. I. Chernov; A. Yu. Gromov; A. M. Kalashnikov; V. I. Karagusov; A. M. Paramonov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In this paper, the process of expansion of wet water vapor in a piston long-stroke low-speed drive of a low-flow compressor unit is considered. The study is carried out on the basis of the developed mathematical model, which includes both the basic thermodynamic equations and the equations describing the process of heat exchange of the working substance with the walls of the working chamber during the expansion process. The results of the calculations carried out reflect the dependences of pressure, temperature and degree of dryness on changes in the volume of the working cavity at various values of the initial degree of dryness in the process of expansion and the duration of the process. An analysis of the results obtained shows that an increase in the cycle time and a decrease in the initial degree of dryness lead to an intensification of the process of condensation of wet steam in the process of expansion and the possibility of obtaining complete condensation of the working fluid.